2013
DOI: 10.1016/j.jacc.2013.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and its Association to Phenotype and Clinical Course in Hypertrophic Cardiomyopathy

Abstract: In HCM patients, extrinsic factors such as obesity are independently associated with increase in LV mass and may dictate progression of heart failure symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
5
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 32 publications
7
96
5
3
Order By: Relevance
“…As recently demonstrated, its prevalence in HCM is remarkably high, reaching almost 40%. Obesity is independently associated with increased LV mass (Figure 3), an adverse prognostic factor in HCM, contributing to more rapid clinical progression and worsening of heart failure symptoms 64. Interestingly, however, LV mass increase in obese patients with HCM seems to merely reflect LV cavity enlargement, physiologically aimed at increasing cardiac output65 to meet the increased requirements of excessive body weight.…”
Section: Acquired Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As recently demonstrated, its prevalence in HCM is remarkably high, reaching almost 40%. Obesity is independently associated with increased LV mass (Figure 3), an adverse prognostic factor in HCM, contributing to more rapid clinical progression and worsening of heart failure symptoms 64. Interestingly, however, LV mass increase in obese patients with HCM seems to merely reflect LV cavity enlargement, physiologically aimed at increasing cardiac output65 to meet the increased requirements of excessive body weight.…”
Section: Acquired Comorbiditiesmentioning
confidence: 99%
“…Obese individuals ( BMI >30) exhibit higher values of LV mass and indexed LV mass. Reprinted from Olivotto et al64 with permission. Copyright ©2013, Elsevier.…”
Section: Acquired Comorbiditiesmentioning
confidence: 99%
“…Th e subanalysis that focused on patients with HCM and a BMI Յ 30 suggested that the inverse relationship between ODI and o 2 peak remains valid throughout the BMI spectrum. Given the association between obesity and functional disability in HCM, 28 and the increase in the likelihood of SDB with increasing obesity, 26 it would be important for future studies to examine to what degree underdiagnosed SDB in overweight and obese patients with HCM may actually be contributing to the functional disability. Because evidence from non-HCM studies suggested that weight loss improved but did not fully normalize SDB, 29 and also because lifestyle modifications can oft en be diffi cult to implement and maintain, diagnosis and treatment of SDB may be recommended, in conjunction with safe rehabilitative exercise and a healthy diet, to overweight patients with HCM.…”
Section: Noncardiac Factorsmentioning
confidence: 99%
“…1 Obesity has been shown to have adverse effects on the cardiovascular system, promote atherosclerotic plaques, 2 and worsen outcomes in patients with coronary artery disease. 3 Obesity can also induce cardiac remodeling, 4 particularly left ventricular (LV) hypertrophy and diastolic dysfunction, 5 which is directly related to mortality. 6 …”
Section: Introductionmentioning
confidence: 99%